2016
DOI: 10.1186/s12885-016-2411-1
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage phenotypic subtypes diametrically regulate epithelial-mesenchymal plasticity in breast cancer cells

Abstract: BackgroundMetastatic progression of breast cancer involves phenotypic plasticity of the carcinoma cells moving between epithelial and mesenchymal behaviors. During metastatic seeding and dormancy, even highly aggressive carcinoma cells take on an E-cadherin-positive epithelial phenotype that is absent from the emergent, lethal metastatic outgrowths. These phenotypes are linked to the metastatic microenvironment, though the specific cells and induction signals are still to be deciphered. Recent evidence suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 46 publications
6
56
0
Order By: Relevance
“…Further, EGF and IGF-1 enhances expression of transcription factors associated with pluripotency, proliferation, and EMT (Castano et al, 2013). Macrophage phenotypic subtypes completely regulate epithelial-to-mesenchymal plasticity in breast cancer cells (Yang et al, 2016). Co-culturing of epithelial and mesenchymal cell lines with macrophages revealed that M2 macrophages might impart outgrowth and M1 macrophages may contribute to dormancy behaviors in metastatic breast cancer cells.…”
Section: Metastatic Nichesmentioning
confidence: 99%
“…Further, EGF and IGF-1 enhances expression of transcription factors associated with pluripotency, proliferation, and EMT (Castano et al, 2013). Macrophage phenotypic subtypes completely regulate epithelial-to-mesenchymal plasticity in breast cancer cells (Yang et al, 2016). Co-culturing of epithelial and mesenchymal cell lines with macrophages revealed that M2 macrophages might impart outgrowth and M1 macrophages may contribute to dormancy behaviors in metastatic breast cancer cells.…”
Section: Metastatic Nichesmentioning
confidence: 99%
“…It is noteworthy that macrophages can be classified into two major categories – classically activated M1 macrophages are linked with tumoricidal functions, and alternatively activated M2 macrophages are involved in tumor promotion [145]. Fascinatingly, TAMs have been considered as M2 macrophages, which could promote the EMT [145–147]. A recent study has shown that leptin may promote breast cancer progression by stimulating M2 macrophages [148].…”
Section: Female Reproductive System Cancersmentioning
confidence: 99%
“…6 Prior studies have revealed that M2 macrophages could induce the epithelial-mesenchymal transition (EMT) process and promote tumor metastasis. 7,8 However, the molecular mechanism by which M2 macrophages play in the invasion and metastasis of ESCC remains largely unknown.…”
mentioning
confidence: 99%